Changes in protein interactions in pasteurized milk during cold storage. (April 2020) - Li, Xing; Li, Lin; Ma, Ying; Wang, Rongchun; Gu, Yuxiang; Day, Li
Abstract: The changes in the major proteins of pasteurized milk (85 °C/15 s) during storage at 4 °C for 7 days were investigated. Parameters such as particle size, zeta potential, morphology of the casein micelles, protein micelle and serum phase distribution, surface hydrophobicity and rheological properties of pasteurized milk were determined. The results showed that there were two major noticeable changes of protein interactions. The first was the heat-induced interaction of whey proteins with casein micelles leading to an increase in the micelle size by 17–34 nm and negative increase in the zeta potential. The second appears to be caused by the progress of protein aggregation which was most evident between 5 and 7 days of cold storage. The protein aggregation was observed using TEM. It showed another measurable increase of the micelle size to 18–42 nm and reduction in the milk flow behavior index. The amounts of κ-casein (κ-CN) and β-lactoglobulin (β-LG) increased gradually in the micelle phase during storage suggesting that re-association of β-LG/κ-CN complexes with the micelles resulted in changes in the surface hydrophobicity of proteins in pasteurized milk during storage. Moreover, the consistency coefficient increased and the flow behavior index decreased gradually throughout the 7 days of storage, which is another indication of increased protein interactions due to re-association of denatured whey proteins and/or β-LG/κ-CN complexes with the micelles. This study showed the association and aggregation of milk proteins continued during the storage of pasteurized milk, which might have implication for the nutritional quality of milk with length of storage. Highlights: The interactions in milk proteins occurred with pasteurized milk during cold storage. Whey proteins associated with the micelle surface after the heat treatment and with up to 1 day. Heated-induced protein complexes re-associated with casein micelles during the storage.